Troubleshooting TCP/IP - Miller, Mark 1955- (M&T Books, 1999)
Detailed professional's guide to all the key protocols need to configure and troubleshoot your TCP/IP internetwork. Packed with illustrations, case studies, examples, and reference appendixes, this book also provides highly detailed case studies of the various layers of Internet addressing as well as a layer-by-layer study of the ARPA architectural model. From ISDN connections to HTTP Web page access, this indispensable reference manual delivers all the tools, techniques, and proven solutions you need to keep your internetwork operating effectively.